2021
DOI: 10.24903/sj.v6i2.782
|View full text |Cite
|
Sign up to set email alerts
|

Visually Impaired Novice Translators in Using Translation Techniques

Abstract: Background: This study aims to determine the translation techniques used by visually impaired translators in translating popular scientific texts. Visually impaired translators were used as the subjects of this study because when compared to sighted translators, visually impaired translators had a different way of doing translation activities. The difference in this performance is influenced using text-to-speech tools they use. Apparently, this phenomenon has not been discussed by various specialized tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This is also supported by findings from Nugroho et al (2016) that translators who have physical limitations and have good skills in using English cannot be as creative as translators who lack an understanding of English. However, it is possible that the translation results from visually impaired translators are less effective, because most of them translate scientific texts by reading word-for-word (Nugroho et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is also supported by findings from Nugroho et al (2016) that translators who have physical limitations and have good skills in using English cannot be as creative as translators who lack an understanding of English. However, it is possible that the translation results from visually impaired translators are less effective, because most of them translate scientific texts by reading word-for-word (Nugroho et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the process-oriented researches found in this study are Purnomo et al (2020) and Nugroho et al (2021). Purnomo et al (2020) conducted a study that involved nine translators of children's picture books.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Nugroho, Muljono, & Nababan, (2021) regarding translation techniques performed by blind translators identified that visually impaired translators utilize literal translation and discursive creation techniques. The employment of literal translation produces rigid translation, whereas the use of discursive creation resulted in a shift in meaning between the source language and the target language.…”
Section: Discussionmentioning
confidence: 99%